Adsorption of ammonium from aqueous solution using coffee husk-derived activated charcoal composite with Fe3O4 - Thuy-Tien Do; Huu-Tap Van; Quang-Huy Pham; Thi-Hien Nguyen (Results in Surfaces and Interfaces)
In this study, a composite materials between Fe3O4 and activated charcoal from coffee husks (denoted FO@ACH) was synthesized using co-precipitate and hydrothermal methods for the removal of ammonium from aqueous solutions. The characteristics of FO@ACH were characterized evaluated by scanning electron microscopy (SEM) and Fourier transform infrared spectra (FTIR). The ammonium adsorption process of FO@ACH was investigated through batch experiments, assessing parameters such as solution pH, material dosage, contact time and initial ammonium concentration. Results indicate that FO@ACH effectively adsorbs ammonium, attributed to the functional groups present on the composite surface. The maximum ammonium adsorption capacity of FO@ACH was 29.41 mg g−1 at an initial ammonium concentration of 20 mg.L−1, pH 6, material dosage of 1 g.L−1 and contact time of 20 min. The FO@ACH composite material shows strong potential as an effective agent for ammonium removal in water treatment applications. The experimental adsorption data by FO@ACH were best fitted by the pseudo-second-order kinetic model (R2 = 0.9927, qm = 23.36 mg g−1) and the Langmuir isotherm model (R2 = 0.9986, qm = 29.41 mg g−1), demonstrating optimal alignment with the observed results. The FO@ACH composites exhibit commendable reusability for ammonium adsorption, maintaining over 50% of their initial adsorption capacity following five cycles.